Evaluation of the efficiency of educational services in the city of Khabat (a study in the geography of services): (Raparin Journal of Humanities (RJH), 2024)
main factor in the change towards the future and the transition from backwardness to progress. It is directly related to man's efficiency, skill and ability to produce work. Education is one of the important indicators that reflects the ability of individuals to think in an organized manner and to bring about some economic, social, and cultural changes that lead to progress and prosperity, without which urbanization would not have been able to develop, and the city would also develop experiences and flourish in education. It is noted that the higher the educational level, the higher the productive efficiency, the higher the income level, and the higher the demand for education at all stages, and this has resulted in an increase in economic and political development. Education is rooted in civilization and is a means of wealth and energy and a manifestation of government services, and is the basis for preparing the individual to become a useful building block in society.